Ocular side effects of chloroquine in patients with rheumatoid arthritis, systemic lupus erythematosus and scleroderma - Leecharoen S. (2014)
Objective: Ocular complication is a major long term adverse event of chloroquine. The present study was carried out to determine the ocular side effects of chloroquine in patients with rheumatic diseases. Material and Method: Medical records of patients with rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and scleroderma (Scl), who received chloroquine for their treatment, at the Division of Rheumatology, Faculty of Medicine, Chiang Mai University between 1 January 1992 and 31 August 2005 were reviewed. Only patients who were older than 16 years, had a clear total accumulative dose and duration of chloroquine therapy, and a regular ophthalmologic examination by ophthalmologists were included in the present study. Results: One hundred and thirty-nine patients (54, 49, and 36 cases of RA, SLE and Scl, respectively) were studied. Forty-eight patients (34.5%) had ocular adverse effects (retinopathy in 37 and corneal deposition in 13 while two patients had both defects). There was no statistical difference in age, mean lean body weight adjusted daily dose, total dosage, and duration of treatment between those with and without ocular side effects. However, those with ocular side effects had significantly lower creatinine clearance (66.9 ± 26.9 vs 72.3 ± 20.0 ml/min, p = 0.046). Conclusion: Ocular side effects of chloroquine were more common in patients with connective tissue diseases who had decreased creatinine clearance. The use of chloroquine in patients with impaired renal function should be of greater concern.